What Is Wellbeing? - Jarden, A; Roache, A (MDPI AG, 2023)
The human interest in 'wellbeing' dates back thousands of years, with complex indigenous understandings [...].
Keywords: 39 Education; 3904 Specialist Studies In Education; 44 Human Society; Generic health relevance; 3 Good Health and Well Being; Toxicology; Humans; Health Status; Mental Health; Humans; Mental Health; Health Status; Humans; Health Status; Mental Health